Prediction of Peri-Urban Land Use in Sleman Regency and Its Suitability towards Spatial Planning - Amesta Ramadhani; Laksmi Yustika Devi; Andri Prasetiyo; Aisyah Yustikaningtyas Harnadi; Rindiani Amelia (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2023)
The development of Yogyakarta city as the growth center in the Yogyakarta urban area has resulted in significant physical changes on its peri-urban, especially in Sleman Regency. The peri-urban area is a transition zone between urban and rural features. This area often experiences dramatic changes in socio-economic as well as spatial structure conditions such as land conversion. The rate of land conversion in the peri-urban area of Sleman Regency happened mostly due to the need for housing, including the need for migrants. This land use dynamic needs to be understood to anticipate uncontrolled land use changes in the future, especially in peri-urban as it has been widely developed for housing in recent years. Therefore, this study seeks to simulate land use changes in the peri-urban area of Sleman Regency in 2041 using Land Change Modeler. The variables used in this study consisted of driving factors (distance to roads, distance to settlements, and population density) and limiting factors (distance to rivers, environmental physical conditions, and determination of protected areas). Based on the simulation results, there will be a significant increase in residential areas from agricultural areas. On the contrary, green areas (forest, bush, and open land) experience a decrease. Simulation of future land use and suitability is the first step for land use policy-making. By knowing future land use, this study can be beneficial for land use control policies for sustainable land use, especially in rapidly developed areas.